Pulmonary responses in rat lungs after intratracheal instillation of 4 crystal forms of titanium dioxide nanoparticles. Issue 6 (29th November 2016) - Okada, Takami; Ogami, Akira; Lee, Byeong Woo; Kadoya, Chikara; Oyabu, Takako; Myojo, Toshihiko
Abstract : Objective: Titanium dioxide nanoparticles are widely used as UV filters in cosmetics and as a photocatalyst. We evaluated pulmonary responses to different crystal forms of TiO2 nanoparticles. Methods: We used 4 different TiO2 samples with similar specific surface areas (anatase, rutile, amorphous, and P25). Each sample was suspended in distilled water and intratracheally instilled to male Wister rats at the dose of 1 mg per rat. Five rats per group were sacrificed at 3 days, 1 month, and 6 months after instillation, and bronchoalveolar lavage fluid was collected from the right lung to determine the total cell count and polymorphonuclear cell (PMN) counts. The left lung tissues were stained with hematoxylin and eosin for the evaluation of inflammation and with elastica van Gieson for the evaluation of collagen deposition. Results: The total cell counts and PMN counts of the amorphous and P25 of four samples showed a significant increase compared with the control group at 3 days after instillation. The inflammation rate of P 25 also showed a significant increase compared with controls at 3 days. The collagen deposition rate in the alveolar duct of P25 increased significantly compared with controls from 3 days to 6 months. The other samples showed a mild response after instillation. Conclusion: Although the TiO2 nanoparticles used in this study had similar specific surface areas, there were different inflammatory responses in the rat lungs. Other factors, such as different production processes or the surface activities of particles, may have been responsible for the different responses.